Age-related Trends in Multidrug Resistance and Extended-spectrum Beta-lactamase Production among Patients with Community-acquired Urinary Tract Infections - Murad Ali, Syed Qasim Shah, Amjad Ali, Sara Shamshad, Humaira Zakir, Hamidullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Urinary tract infections (UTIs) are among the most common community-acquired infections worldwide. The increasing prevalence of multidrug-resistant (MDR) organisms and extended-spectrum beta-lactamase (ESBL) producers in these infections has become a major public health concern, especially in regions with unregulated antibiotic use. Objective: This study aimed to determine the frequency of EDR and ESBL expression among bacterial isolates from patients with community-acquired UTIs, and to explore the association of resistance with age and clinical history. Methods: An observational study was conducted over 11 months at Mardan Medical Complex, Mardan including 167 patients presenting with symptoms of UTI from May 2022 to March 2023. ‘Midstream urine samples were collected and cultured using standard microbiological procedures’. ‘Antibiotic susceptibility testing was performed using the Kirby-Bauer disk diffusion method following CLSI guidelines’. ESBL production was confirmed using the combination disk method. Clinical and demographic data were analyzed to identify factors associated with resistance. Results: Escherichia coli was the most frequently isolated organism (62.3%), followed by Klebsiella pneumoniae (17.4%). Overall, 71.9% of isolates were found to be multidrug-resistant, and 50.9% produced ESBLs. Older age, comorbidities, and recent antibiotic use were significantly associated with both MDR and ESBL positivity (p < 0.05). Resistance was particularly high against ciprofloxacin, trimethoprim-sulfamethoxazole, and ceftriaxone, while carbapenems remained largely effective. Conclusion: The study highlights a high burden of MDR and ESBL-producing pathogens in community-acquired UTIs. These findings underscore the urgent need for rational antibiotic use and local surveillance data to guide empirical therapy. Age and clinical history should be considered when selecting treatment in outpatient settings. Keywords: Urinary tract infection, EDR, ESBL, community-acquired infection, Escherichia coli, antibiotic resistance, Pakistan, uropathogens